2016
DOI: 10.1108/ribs-06-2014-0072
|View full text |Cite
|
Sign up to set email alerts
|

Social capital: mediator of financial literacy and financial inclusion in rural Uganda

Abstract: Purpose The purpose of this paper is to examine the mediating role of social capital in financial literacy and financial inclusion relationship in rural Uganda. The major aim is to establish the role of social capital in the relationship between financial literacy and financial inclusion. Design/methodology/approach The paper adopts and uses MedGraph programme (Excel version 3.0), Sobel and Kenny and Baron tests to test the mediation effect of social capital in the relationship between financial literacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 52 publications
10
42
3
6
Order By: Relevance
“…Policymakers, service providers, and financial educators ought to take cognizance of social influences to promote financial inclusion in countries like Uganda. This recommendation supports Okello et al (2016), who found that financial literacy alone had no significant impact on financial inclusion but rather that social capital's introduction fully mediated the relationship between financial literacy and financial inclusion in rural Uganda. Bandura (1986) postulates that learning also occurs when people, through interactions, observe others, imitate them, and seek to model specific behaviors, our results highlight the importance of social interactions in synthesizing knowledge on formal financial products, before actual product uptake.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Policymakers, service providers, and financial educators ought to take cognizance of social influences to promote financial inclusion in countries like Uganda. This recommendation supports Okello et al (2016), who found that financial literacy alone had no significant impact on financial inclusion but rather that social capital's introduction fully mediated the relationship between financial literacy and financial inclusion in rural Uganda. Bandura (1986) postulates that learning also occurs when people, through interactions, observe others, imitate them, and seek to model specific behaviors, our results highlight the importance of social interactions in synthesizing knowledge on formal financial products, before actual product uptake.…”
Section: Discussionsupporting
confidence: 65%
“…In agreement, Idris et al (2013) found that financial literacy accounted for variations in individual behavior and financial outcomes associated with credit, investment, and saving behaviors. Literature is also replete with findings on significant relationships established between financial literacy and the broader concept of financial inclusion (Okello et al, 2016;Grohmann et al, 2017). These studies support Wachira and Kihiu (2012) findings, who established a higher probability for people with lower levels of financial literacy to have a higher likelihood of financial exclusion.…”
Section: Financial Literacy and The Use Of Formal Financial Servicesmentioning
confidence: 68%
“…The inaccessibility to formal financial services negatively impacts livelihoods in Uganda by increasing transaction costs and risks, limited market exchange and limiting opportunities for households to save. Therefore according to Okello, Ntayi, Munene and Nabeta [5], the absence of effective social capital financing in Uganda, financial literacy mail fails to enhance the level of financial inclusion among rural households. Thus the need for all economic planning to be future based signifying that food security matters are sustainable for every community leading to self-reliance.…”
Section: Savingsmentioning
confidence: 99%
“…For example, when young adults (ages [18][19][20][21][22][23][24] in the United States of America were asked the high-school level course that most benefited their lives, more than 50% responded in favor of "money management". Georgia, Idaho, and Texas mandated financial education; after three years of implemention, all the three observed increment in credit scores and lower delinquency rates within credit accounts [5]. Thus, constructive individual and institutional research has emphasized need for financial literacy to a code culture status across businesses [6].…”
Section: Introductionmentioning
confidence: 99%
“…There have not been adequate studies to determine individual levels of financial literacy in Uganda. A few studies such as Bongomin et al (2017) examined the components of financial literacy, while Bongomin et al (2016) assessed the mediating effects of social capital on the relationship between financial literacy and financial inclusion. Kasalirwe & Lokina (n.d) evaluated the levels of financial literacy and its impact on investment choices in Uganda.…”
Section: Introductionmentioning
confidence: 99%